Lithium ion battery

By adjusting the tensile strength and elongation of the negative and positive current collector in the lithium-ion battery, as well as the bonding strength between the separator and the electrode sheet, the problem of expansion and disengagement of the electrode sheet during the charging and discharge of the lithium-ion battery is solved, and the battery is improved safety performance.

CN119208750APending Publication Date: 2024-12-27ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411386252.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the charging and discharging of lithium ions, the negative electrode sheet expands due to the release and embeddedness of lithium ions, which easily leads to the separation of the separator and the negative electrode sheet, causing battery short circuit and safety risks.

Method used

By adjusting the tensile strength and elongation of the negative electrode current collector, the tensile strength and elongation of the positive electrode current collector, and regulating the bonding strength between the diaphragm and the electrode sheet, we can meet specific relationships to improve the deformation resistance of the electrode sheet and Adhesion force prevents the pole sheet from expanding and disengaging.

Benefits of technology

It effectively reduces the deformation and expansion of the negative electrode plate, reduces the separation between the diaphragm and the electrode plate, improves the safety performance of the battery, and prevents short circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208750A_ABST
    Figure CN119208750A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery preparation, and particularly relates to a lithium ion battery. The lithium ion battery comprises a positive pole piece, a negative pole piece and a diaphragm arranged between the positive pole piece and the negative pole piece, the positive pole piece at least comprises a positive current collector; the tensile strength A1 of the negative current collector, the elongation B1 of the negative current collector, the tensile strength A2 of the positive current collector and the elongation B2 of the positive current collector meet the relational expression 1, so that the negative pole piece can resist deformation caused by lithium removal and lithium intercalation, the deformation quantity of the negative pole piece is reduced, the pole piece is prevented from expanding, and the service life of the negative pole piece is prolonged. The separation of the negative pole piece and the diaphragm is reduced, the short circuit of the battery is prevented, and the safety performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery preparation, and in particular relates to a lithium ion battery. Background Art

[0002] Lithium-ion batteries have the advantages of being lightweight, high specific energy, no memory effect, and good cycle performance, and are widely used in digital, energy storage, power, military aerospace, and communication equipment. With the widespread application of lithium-ion batteries, consumers have put forward higher requirements for the energy density, cycle life, high temperature performance, and safety performance of lithium-ion batteries.

[0003] Due to the release and embedding of lithium ions during the charge and discharge process, the negative electrode plate is deformed and causes the plate to expand. The expansion of the negative electrode plate can also cause the diaphragm and the negative electrode plate to fall off, causing a battery short circuit and causing safety risks. Summary of the invention

[0004] The present invention provides a lithium-ion battery, which can not only solve the problem of negative electrode plate expansion, but also reduce the risk of separation between the separator and the negative electrode plate.

[0005] To this end, the present invention provides the following technical solutions.

[0006] The present invention provides a lithium ion battery, the lithium ion battery comprising a positive electrode sheet, a negative electrode sheet and a separator arranged between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer located on at least one side surface of the positive electrode current collector; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer located on at least one side surface of the negative electrode current collector; the tensile strength A of the negative electrode current collector is 1 , the elongation B of the negative electrode collector 1 %, the tensile strength A of the positive electrode current collector 2 , the elongation B of the positive electrode collector 2 %, the bonding strength C between the separator and the negative electrode sheet 1 Satisfies the relationship 1:

[0007]

[0008] The A 1 Satisfaction: A 1 ≥300MPa; B 1 Satisfaction: 2% ≤ B 1 %≤10%; 2 Satisfaction: A 2 ≥180MPa; B 2 Satisfaction: 1% ≤ B 2 %≤10%; 1 Satisfy: 1N / m≤C 1≤80N / m.

[0009] The technical solution of the present invention has the following advantages:

[0010] 1. The lithium-ion battery provided by the present invention comprises a positive electrode sheet, a negative electrode sheet and a separator arranged between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet at least comprises a positive electrode current collector; the tensile strength A of the negative electrode current collector is 1 , the elongation B of the negative electrode collector 1 , the tensile strength A of the positive electrode current collector 2 , the elongation B of the positive electrode collector 2 , the bonding strength C between the separator and the negative electrode sheet 1 Satisfying equation 1 can make the negative electrode plate resist deformation caused by lithium removal and lithium insertion, reduce the deformation of the negative electrode plate, prevent the plate from expanding, reduce the separation of the negative electrode plate and the separator, prevent the battery from short circuit, and improve the safety performance of the battery.

[0011] 2. The lithium-ion battery provided by the present invention regulates factors such as the crystal surface strength of the negative electrode current collector, the pore size distribution of the diaphragm, the porosity of the diaphragm, the air permeability of the diaphragm, the bonding strength between the diaphragm and the negative electrode sheet and makes them satisfy equation 2, which can improve the bonding between the diaphragm and the negative electrode sheet, improve their bonding strength, and reduce the peeling and falling off of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0013] Figure 1 This is a schematic structural diagram of a positive electrode sheet according to Embodiment 1 of the present invention;

[0014] Figure 2 This is a schematic diagram of the structure of the negative electrode sheet of Example 1 of the present invention;

[0015] Figure 3 This is a schematic structural diagram of a diaphragm according to Example 1 of the present invention;

[0016] Figure 4 This is a schematic structural diagram of a battery in Example 1 of the present invention;

[0017] Reference numerals:

[0018] 11 - positive electrode current collector; 12 - positive electrode active material layer; 21 - negative electrode current collector; 22 - negative electrode active material layer; 31 - base film; 32 - ceramic layer; 33 - glue coating layer. DETAILED DESCRIPTION

[0019] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0020] In the description of the present invention, it should be noted that the terms "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.

[0021] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0022] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0023] The present invention provides a lithium-ion battery, which can reduce the deformation of the pole piece due to lithium removal and lithium insertion during the charging and discharging process, reduce the expansion rate of the negative pole piece, reduce battery short circuit, and improve battery safety performance. The technical solution adopted by the present invention is as follows.

[0024] In a first aspect, the present invention provides a lithium ion battery, the lithium ion battery comprising a positive electrode sheet, a negative electrode sheet and a separator arranged between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet at least comprises a positive electrode current collector; the tensile strength A of the negative electrode current collector is 1 , the elongation B of the negative electrode collector 1 %, the tensile strength A of the positive electrode current collector 2 , the elongation B of the positive electrode collector 2 %, the bonding strength C between the separator and the negative electrode sheet 1 Satisfies the relationship 1:

[0025]

[0026] The A 1 Satisfaction: A 1 ≥300MPa; B 1 Satisfaction: 2% ≤ B 1 %≤10%; 2 Satisfaction: A 2 ≥180MPa; B 2 Satisfaction: 1% ≤ B 2 %≤10%; 1 Satisfy: 1N / m≤C 1 ≤80N / m.

[0027] It is understood in the art that during the battery charging and discharging process, the release and insertion of lithium ions will cause the pole piece to deform, the negative pole piece to expand, and the separator and the negative pole piece to separate, resulting in a short circuit in the battery and reducing the safety performance of the battery. 1 ≥300MPa, the elongation B of the negative electrode collector 1 Satisfaction: 2% ≤ B 1 %≤10%, the tensile strength A of the positive electrode current collector 2 ≥180MPa, the elongation B of the positive electrode current collector 2 Satisfaction: 1% ≤ B 2 %≤10%, regulating the tensile strength and elongation of the positive electrode collector and the negative electrode collector to satisfy the relationship 1, which can make the negative electrode sheet resist the deformation caused by lithium removal and lithium insertion, reduce the deformation of the negative electrode sheet, prevent the sheet from large irreversible expansion, reduce the separation of the negative electrode sheet and the diaphragm, prevent the battery from short circuit, and improve the safety performance of the battery.

[0028] The applicant found that the tensile strength of the negative electrode current collector is lower than 300MPa. The strength is too low to resist the deformation, resulting in a large expansion rate, causing a short circuit in the battery and causing safety risks. The tensile strength of the positive electrode current collector is lower than 180MPa. The strength is too low to resist the deformation. It is understandable that during the charge and discharge process of the battery, the negative electrode will expand and shrink significantly. Since the battery is an integral structure, the positive electrode is affected by the expansion of the negative electrode and deforms. Therefore, the negative electrode current collector and the positive electrode current collector simultaneously meet A 1 ≥300MPa, A 2 ≥180MPa can prevent the electrode from experiencing large irreversible expansion, reduce the separation of the electrode and the diaphragm, and thus improve the safety performance of the battery.

[0029] As an example, the strength A of the negative electrode current collector 1330MPa, 400MPa, 500MPa, 600MPa, 700MPa, 800MPa, 900MPa, 990MPa or within a range of any two of the above values. As an example, the strength A of the positive electrode current collector 2 is 200MPa, 220MPa, 240MPa, 260MPa, 280MPa, 300MPa, 330MPa, 340MPa, or is within a range of any two of the above values. As an example, the elongation B of the negative electrode current collector is 1 % is 3%, 4%, 5%, 6%, 7%, 8%, 9%, 9.5% or within the range of any two of the above values. As an example, the elongation B of the positive electrode current collector is 2 % is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 9.5% or within the range of any two of the above values. 1 Satisfy: 300MPa≤A 1 ≤1000MPa; A 2 Satisfy: 180MPa≤A 2 When ≤350MPa, the current collector is a rigid material that can resist deformation during the charge and discharge process, further reducing battery short circuits and improving battery performance.

[0030] In an optional embodiment, the strength A of the negative electrode current collector is 1 is the average value of the tensile strength in the TD and MD directions; preferably, the tensile strength in the TD direction of the negative electrode current collector is not less than 300MPa; preferably, the tensile strength in the MD direction of the negative electrode current collector is not less than 300MPa; it can be understood that the tensile strength of the negative electrode current collector is related to its tensile strength in the TD direction and the MD direction, and regulating the tensile strength in the TD direction and the MD direction can enhance the negative electrode current collector's ability to resist deformation. As an example, the tensile strength in the TD direction of the negative electrode current collector is 330MPa, 400MPa, 500MPa, 600MPa, 700MPa, 8000MPa, 900MPa, 1000MPa or is within the range of any two of the above values, preferably not less than 450MPa. The tensile strength of the negative electrode current collector in the MD direction is 330 MPa, 400 MPa, 500 MPa, 600 MPa, 700 MPa, 8000 MPa, 900 MPa, 1000 MPa or within a range formed by any two of the above values, and is preferably not less than 450 MPa.

[0031] In an optional embodiment, the elongation B of the negative electrode current collector is 1% is the average value of the elongation in the TD and MD directions; preferably, the elongation in the TD direction of the negative electrode current collector is not less than 2%; preferably, the elongation in the MD direction of the negative electrode current collector is not less than 2%; it can be understood that the elongation of the negative electrode current collector is related to its elongation in the TD direction and the MD direction, and regulating the elongation in the TD direction and the MD direction can make the negative electrode current collector resist the deformation produced. As an example, the elongation in the TD direction of the negative electrode current collector is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or in the range of any two of the above values, preferably not less than 3.5%. The elongation in the MD direction of the negative electrode current collector is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or in the range of any two of the above values, preferably not less than 3.5%.

[0032] In an optional embodiment, the strength A of the positive electrode current collector is 2 is the average value of the tensile strength in the TD and MD directions; preferably, the tensile strength in the TD direction of the positive current collector is not less than 180MPa; preferably, the tensile strength in the MD direction of the positive current collector is not less than 200MPa; it can be understood that the tensile strength of the positive current collector is related to its tensile strength in the TD and MD directions, and regulating the tensile strength in the TD and MD directions can make the positive current collector resist the deformation. As an example, the tensile strength in the TD direction of the positive current collector is 180MPa, 200MPa, 220MPa, 240MPa, 260MPa, 280MPa, 300MPa, 330MPa, 340MPa or within the range of any two of the above values. The tensile strength of the positive electrode current collector in the MD direction is 180 MPa, 200 MPa, 220 MPa, 240 MPa, 260 MPa, 280 MPa, 300 MPa, 330 MPa, 340 MPa or within a range formed by any two of the above values.

[0033] In an optional embodiment, the elongation B of the positive electrode current collector is 2% is the average value of the elongation in the TD and MD directions; preferably, the elongation in the TD direction of the positive electrode collector is not less than 1%; preferably, the elongation in the MD direction of the positive electrode collector is not less than 1%. It can be understood that the elongation of the positive electrode collector is related to its elongation in the TD direction and the MD direction, and regulating the elongation in the TD direction and the MD direction can make the positive electrode collector resist the deformation produced. As an example, the elongation in the TD direction of the positive electrode collector is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or in the range of any two of the above values. The elongation in the MD direction of the positive electrode collector is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or in the range of any two of the above values.

[0034] It should be noted that the strength of the negative current collector, the strength of the positive current collector, the elongation of the negative current collector, the elongation of the positive current collector, the bonding strength between the diaphragm and the negative electrode sheet, and the bonding strength between the diaphragm and the positive electrode sheet are all tested according to methods known in the art, and the results of different test methods are basically the same. List a test method, such as strength and elongation, refer to the GB-228-87 test method, and the test parameters are set to a gauge length of 50mm and a tensile speed of 10-50mm / min. Test method for the bonding strength between the diaphragm and the electrode sheet: Cut a sample of a 100mm long and 15mm wide current collector and a diaphragm bonded together; fix the diaphragm on the upper and lower clamps of a universal tensile machine respectively; then peel the sample 180°, the test speed is 100mm / min, the test displacement distance is 80mm, and the diaphragm bonding strength is obtained through the output data of the tensile machine.

[0035] In an optional embodiment, the surface density of the negative electrode current collector is not less than 26 mg / m 2 It is understood that the surface density of the negative electrode current collector is not less than 26 mg / m 2 The negative electrode current collector has a more suitable thickness. It is well known to those skilled in the art that the negative electrode current collector can be made of copper foil, nickel foil, titanium foil, iron-nickel alloy foil, etc. As an example, the surface density of the negative electrode current collector is 26 mg / m 2 , 27mg / m 2 , 28mg / m 2 , 29mg / m 2 , 30mg / m 2 , 31mg / m 2 , 32mg / m 2 , 33mg / m 2 , 34mg / m 2 , 40mg / m 2 48mg / m 2 , 55mg / m 2, 65mg / m 2 , 75mg / m 2 , 89.4mg / m 2 Or within the range formed by any two of the above values. It is understood that the surface density refers to the weight per unit area.

[0036] In an optional embodiment, the thickness of the negative electrode current collector is not less than 3 μm; as an example, the thickness of the negative electrode current collector is 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or within a range formed by any two of the above values. It is understood that the negative electrode current collector is related to the battery energy density. The thinner the negative electrode current collector, the higher the battery energy density.

[0037] In an optional embodiment, the surface density of the positive electrode current collector is not less than 16 mg / m 2 It is understandable that the surface density of the positive electrode current collector will affect the thickness of the positive electrode current collector. The surface density of the positive electrode current collector is not less than 16 mg / m 2 , so that it can have a relatively suitable thickness. It is well known to those skilled in the art that the positive electrode current collector is aluminum foil or the like. As an example, the surface density of the positive electrode current collector is 16 mg / m 2 , 20mg / m 2 , 23mg / m 2 , 26mg / m 2 , 27mg / m 2 , 28mg / m 2 , 29mg / m 2 , 30mg / m 2 , 31mg / m 2 , 32mg / m 2 , 33mg / m 2 , 34mg / m 2 , 38mg / m 2 42mg / m 2 46mg / m 2 , 50mg / m 2 , 54mg / m 2 Or within the range formed by any two of the above values.

[0038] It is understandable that the surface density of the current collector is a conventional parameter of the current collector. When the current collector is determined, the surface density is also determined accordingly. It should be noted that the surface density of the negative electrode current collector and the positive electrode current collector is obtained by testing according to methods known in the art. For example, a punching machine with a punching diameter of 12mm / 16mm is used to punch out small discs of the current collector without any material attached, and the weight is recorded m; the area of ​​the punched small disc is calculated according to the diameter of the punched small disc, and the disc area s is recorded; the current collector surface density is obtained using m / s.

[0039] In an optional embodiment, the thickness of the positive electrode current collector is not less than 6 μm; as an example, the thickness of the positive electrode current collector is 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm or within a range formed by any two of the above values.

[0040] In an optional embodiment, the negative electrode current collector contains doping elements; the doping elements include at least one of Cr, Fe, Mg, Mn, Sb, Si, Sn, Ti and Zn; and the content of the doping elements in the negative electrode current collector is not higher than 1000 ppm.

[0041] In an optional embodiment, the positive electrode current collector contains doping elements; the doping elements include at least one of Cr, Fe, Mg, Mn, Sb, Si, Sn, Ti and Zn; the content of the doping elements in the positive electrode current collector is not higher than 10000ppm. It is understood that controlling the doping elements of the positive and negative electrode current collectors can effectively control the various physical properties of the current collectors such as tensile elongation. It is also understood that the positive and negative electrode current collectors are well known in the art.

[0042] In an optional embodiment, the positive electrode plate includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. The positive active material layer is a conventional structure in the art, and the raw materials are selected from conventional raw materials in the art. Specifically, the components of the positive active material layer include positive active material, conductive agent and binder; the positive active material includes at least one of lithium nickelate, lithium titanate, lithium cobaltate, lithium nickel cobalt manganeseate, lithium nickel cobalt aluminum, lithium iron phosphate and lithium manganeseate; the conductive agent includes at least one of carbon black, carbon nanotubes, conductive graphite and graphene; the binder includes at least one of polyvinylidene fluoride (PVDF), acrylic modified PVDF, polyacrylate polymer, polyimide, styrene butadiene rubber and styrene acrylic rubber. It should be noted that the positive active material, conductive agent and binder are prepared according to the conventional ratio in the art. It should be further noted that the positive active material layer is a one-layer or multi-layer structure; when it is a multi-layer structure, the components of each layer are the same or different.

[0043] In an optional embodiment, a first coating is provided on at least one surface of the positive electrode current collector; preferably, the first coating is provided between the positive electrode current collector and the positive electrode active material layer; the components of the first coating include inorganic filler, conductive agent and binder; the mass ratio of inorganic filler, conductive agent and binder is (60-98):(0-5):(2-40). Optionally, the inorganic filler is coated with a conductive layer, and the inorganic filler has good mechanical strength, stability and heat resistance, and can increase the overall strength of the positive electrode sheet, thereby resisting deformation. The inorganic filler coated with a conductive layer gives the first coating a good conductive network, and due to the excellent dispersibility of the inorganic filler itself, the battery has excellent safety performance while taking into account good cycle performance.

[0044] In an optional embodiment, the inorganic filler is selected from at least one of aluminum oxide, magnesium oxide, titanium oxide, zinc oxide, silicon oxide, boehmite, cobalt oxide, iron phosphate, lithium iron phosphate, lithium nickel cobalt manganese oxide, and lithium iron manganese phosphate; the inorganic filler is preferably boehmite. The resistivity of the inorganic filler coated with the conductive layer is 1Ω·cm-100Ω·cm. As an example, the resistivity of the inorganic filler coated with the conductive layer is 1Ω·cm, 3Ω·cm, 5Ω·cm, 7Ω·cm, 9Ω·cm, 10Ω·cm, 20Ω·cm, 40Ω·cm, 60Ω·cm, 80Ω·cm, 100Ω·cm, or within the range of any two of the above values.

[0045] The average particle size of the inorganic filler coated with the conductive layer is 0.05 μm-5 μm, preferably 100 nm-600 nm. As an example, the average particle size of the inorganic filler coated with the conductive layer is 0.05 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, or in the range of any two of the above values.

[0046] In an optional embodiment, the material of the conductive layer includes at least one of ATO, FTO, ITO and carbon material; wherein ATO is tin dioxide doped with antimony, FTO is tin dioxide doped with fluorine, and ITO is indium oxide doped with tin; the doping amount of antimony in ATO is ≤30%, the doping amount of fluorine in FTO is ≤10%, and the doping amount of tin in ITO is ≤30%.

[0047] In an optional embodiment, the mass content of the conductive layer in the inorganic filler coated with the conductive layer is 2wt%-40wt%, preferably 10wt%-30wt%. As an example, the mass content of the conductive layer is 2wt%, 6wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt% or in the range of any two of the above values. The conductive layer can control the conductivity of the positive electrode sheet. If the conductive layer content is too much, the conductivity is too good and the safety is reduced. If the conductive layer content is too little, the conductivity is reduced and the internal resistance of the battery is increased.

[0048] In an optional embodiment, the surface resistance of the first coating is 1mΩ-1000mΩ, preferably 1mΩ-100mΩ. As an example, the surface resistance of the first coating is 1mΩ, 5mΩ, 10mΩ, 15mΩ, 20mΩ, 30mΩ, 40mΩ, 50mΩ, 60mΩ, 70mΩ, 80mΩ, 90mΩ, 100mΩ, 200mΩ, 300mΩ, 400mΩ, 500mΩ, 600mΩ, 700mΩ, 800mΩ, 900mΩ, 1000mΩ or in the range of any two of the above values. It should be noted that the surface resistance is obtained by testing according to a method known in the art. Here, a test method is listed, but not limited to this method: two probes are contacted with the diaphragm respectively to determine that the contact is good; then a current is applied to the probe to measure the voltage drop of the probe, and according to Ohm's law, the resistance is calculated by the voltage drop and the current value.

[0049] In an optional embodiment, the surface density of the first coating is 0.1 mg / cm 2 -1.5mg / cm 2 , preferably 0.5 mg / cm 2 -1.2mg / cm 2 As an example, the surface density of the first coating is 0.1 mg / cm 2 , 0.3mg / cm 2 , 0.6mg / cm 2 , 0.9mg / cm 2 , 1.2mg / cm 2 , 1.5mg / cm 2 Or within the range formed by any two of the above values. It is understandable that the surface density of the first coating layer will affect the thickness of the first coating layer. The surface density of the first coating layer is 0.1 mg / cm 2 -1.5mg / cm 2 The thickness of the first coating layer may be 0.5 μm to 5 μm.

[0050] In an optional embodiment, the peel strength between the first coating and the positive current collector is 20N / m-1000N / m, preferably 100N / m-500N / m. As an example, the peel force between the first coating and the positive current collector is 20N / m, 50N / m, 80N / m, 110N / m, 140N / m, 170N / m, 200N / m, 230N / m, 260N / m, 290N / m, 320N / m, 350N / m, 380N / m, 410N / m, 440N / m, 470N / m, 500N / m, 600N / m, 700N / m, 800N / m, 900N / m, 1000N / m or in the range of any two of the above values. It should be noted that the peel strength is obtained by testing according to a method known in the art. Here is a test method: cut a 100mm long and 15mm wide positive electrode current collector coated with the first coating as the test sample; fix the test sample on the upper and lower fixtures of the universal tensile machine; peel the sample 180°, the test speed is 100mm / min, and the test displacement distance is 80mm. The peel strength is obtained by converting the parameters measured by the tensile machine.

[0051] In an optional embodiment, the thickness of the first coating of the present invention is 0.1μm-5μm, which can be evenly coated on the surface of the current collector, improve the uniform conductivity of the positive electrode sheet, and help improve the low temperature performance and safety performance of the battery. As an example, the thickness of the first coating is 0.1μm, 0.4μm, 0.7μm, 1.0μm, 1.2μm, 1.5μm, 1.8μm, 2.1μm, 2.4μm, 2.7μm, 3μm, 3.3μm, 3.6μm, 3.9μm, 4.2μm, 4.5μm, 5μm or in the range of any two of the above values, and the thickness of the first coating is preferably 2μm-4μm. It should be noted that the first coating can be provided on one or both sides of the positive current collector; the first coating is a one-layer or multi-layer structure, and when it is a multi-layer structure, the composition of each layer of the coating can be the same or different. It can be understood that the thickness of the first coating refers to the thickness of the coating on the same side of the positive current collector. As an example, the first coating layer is one of a single-layer structure, a two-layer structure, a three-layer structure, etc. When the first coating layer is a multi-layer structure, its preparation method is a common method in the art, such as forming a multi-layer structure by multiple coatings. It is understandable that those skilled in the art determine whether the positive electrode current collector is provided with a first coating layer according to needs.

[0052] In an optional embodiment, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector; the negative electrode active material layer is a one-layer or multi-layer structure. When the negative electrode active material layer is a multi-layer structure, the composition of each layer may be the same or different.

[0053] The composition of the negative electrode active material layer includes active materials, which are common raw materials in the field, such as at least one of carbon-based materials, silicon-based materials, tin-based materials, and titanium-based materials; specifically including at least one of artificial graphite, natural graphite, soft carbon, hard carbon, elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon nitrogen composites, silicon alloys, elemental tin, tin oxide compounds, tin alloys, elemental titanium, titanium oxide compounds, and titanium alloys. It is understood that the composition of the negative electrode active material layer may also include additives, such as conductive agents, binders, and the like. The conductive agent includes at least one of carbon black, carbon nanotubes, and the like, and the content of the conductive agent in the negative electrode active material layer is not higher than 3wt%. The binder includes at least one of SBR binders, PAA binders, and the like, and the content of the binder in the negative electrode active material layer is not higher than 3wt%. The active material, conductive agent, and binder in the negative electrode active material layer are used in conventional dosage ratios in the field.

[0054] In an optional embodiment, at least one surface of the negative electrode current collector is also provided with a second coating; as a preferred embodiment, the second coating is provided between the negative electrode current collector and the negative electrode active material layer, and the second coating is used to improve the dynamics of the lithium ion battery; the thickness of the second coating is 0.01 μm-3 μm; the second coating is a carbon coating, which helps to improve the peel strength of the negative electrode active material layer, reduce the amount of binder in the negative electrode active material layer, and improve the battery energy density and dynamics. As an example, the thickness of the second coating is 0.01 μm, 0.1 μm, 0.5 μm, 1.0 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm or within the range of any two of the above values. It is understood that the thickness of the second coating is the thickness of the coating on the same side of the current collector. It should be noted that the second coating is a one-layer or multi-layer structure, and the second coating structure is designed according to demand. It can also be understood that the components of the second coating include carbon materials and may also include components such as binders. As a preferred embodiment, the negative electrode plate includes a negative electrode current collector and a second coating layer disposed on two surfaces of the negative electrode current collector, and the negative electrode active material layer is disposed on the surface of the second coating layer.

[0055] In an optional embodiment, the negative electrode current collector is provided with a groove; the depth of the groove is not higher than the thickness of the negative electrode current collector; the diameter of the groove is not higher than 100 μm; the spacing between adjacent grooves is 0.05 mm-0.5 mm. It is understood that the negative electrode current collector is provided with a groove, which helps to improve the overall dynamics of the battery. It is understood that those skilled in the art determine whether the negative electrode current collector is provided with a second coating and a groove according to needs.

[0056] In an optional embodiment, the negative electrode current collector and the separator satisfy Relationship 2:

[0057]

[0058] Wherein, I is the intensity of the X-ray diffraction peak of the negative electrode current collector (111), I>10000 counts; F is the pore size distribution of the diaphragm, F satisfies: 20nm≤F≤90nm; E is the air permeability value of the diaphragm, E satisfies: 50s / 100cc≤E≤250s / 100cc; D is the porosity of the diaphragm, D satisfies: 25%≤D%≤50%; C 1 is the bonding strength between the separator and the negative electrode plate, and the C 1 Satisfy: 1N / m≤C 1 ≤80N / m.

[0059] Preferably, I is the intensity of the X-ray diffraction peak of the negative electrode current collector (111) crystal plane.

[0060] The applicant discovered during the research that the separator and the negative electrode sheet will peel off during the charge and discharge process. This is because as the charge and discharge proceed, lithium ions are constantly removed and embedded, causing the sheet to expand and shrink, which in turn causes the separator and the negative electrode sheet to peel off. The present invention regulates factors such as the crystal face strength of the negative electrode collector, the pore size distribution of the separator, the porosity of the separator, the air permeability of the separator, and the bonding strength between the separator and the negative electrode sheet and makes them satisfy the relationship 2, which can improve the bonding between the separator and the negative electrode sheet, improve its bonding strength, and reduce the peeling and falling off of the separator. When each factor is too low and does not meet the requirements of the present invention, the bonding between the separator and the negative electrode sheet is insufficient, the bonding strength is poor, and it is easy to fall off and peel off.

[0061] As an example, the I is 15000 counts, 20000 counts, 25000 counts, 30000 counts, 35000 counts, 40000 counts, 45000 counts, 90000 counts, 100000 counts, or within a range formed by any two of the above values. The E is 52s / 100cc, 80s / 100cc, 110s / 100cc, 140s / 100cc, 170s / 100cc, 200s / 100cc, 240s / 100cc, or within a range formed by any two of the above values. The F is 22nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 88nm, or within a range formed by any two of the above values. The D% is 26%, 30%, 35%, 40%, 45%, 49% or within the range of any two of the above values. 12 N / m, 4 N / m, 6 N / m, 10 N / m, 20 N / m, 30 N / m, 40 N / m, 50 N / m, 60 N / m, 70 N / m, 79 N / m or in a range formed by any two of the above values.

[0062] In an optional embodiment, the bonding strength between the separator and the positive electrode sheet is 1-80N / m; as an example, the bonding strength between the separator and the positive electrode sheet is 1N / m, 3N / m, 7N / m, 10N / m, 20N / m, 30N / m, 40N / m, 50N / m, 60N / m, 70N / m, 80N / m or in the range of any two of the above values. The bonding strength between the separator and the negative electrode sheet and the bonding strength between the separator and the positive electrode sheet are obtained by testing according to methods known in the art, and the results of different testing methods are basically consistent. Here is a test method for the bonding strength between the diaphragm and the pole piece: cut a sample of the current collector and the diaphragm bonded together with a length of 100 mm and a width of 15 mm; fix the diaphragm on the upper clamp and the lower clamp of the universal tensile testing machine respectively; then peel the sample 180°, the test speed is 100 mm / min, the test displacement distance is 80 mm, and the bonding strength between the diaphragm and the pole piece is obtained through the output data of the tensile testing machine.

[0063] In an optional implementation, the EF satisfies: EF>1200; the thickness H of the diaphragm satisfies: 5μm≤H≤15μm.

[0064] As an example, the EF is 1300, 2000, 4000, 6000, 8000, 10000 or in a range formed by any two of the above values. The H is 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 14.5 μm or in a range formed by any two of the above values.

[0065] In an optional embodiment, the diaphragm includes a base membrane;

[0066] Preferably, the base film has a thickness of 3 μm-16 μm, a porosity of 25%-50%, an air permeability of 50s / 100cc-250s / 100cc, and a pore size distribution of 20nm-90nm.

[0067] It is understandable that the porosity, air permeability and pore size distribution of the base film affect the porosity, air permeability and pore size distribution of the separator, which in turn affects the expansion and contraction during the charge and discharge process.

[0068] As an example, the thickness of the base film is 3μm, 6μm, 9μm, 12μm, 16μm or in the range of any two of the above values; the porosity is 25%, 30%, 35%, 40%, 45%, 50% or in the range of any two of the above values; the permeability is 50s / 100cc, 80s / 100cc, 110s / 100cc, 140s / 100cc, 170s / 100cc, 200s / 100cc, 250s / 100cc or in the range of any two of the above values; the pore size distribution is 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or in the range of any two of the above values.

[0069] In an optional embodiment, the diaphragm further includes a coating, the coating is located on at least one surface of the base film, and the coating includes at least one of a ceramic layer and a rubber layer; the ceramic layer and the rubber layer are provided on the base film, which can improve the bonding strength between the diaphragm and the negative electrode plate, increase the bonding force, and reduce the risk of the diaphragm falling off or peeling off. It is understandable that the base film is selected from the known membrane materials in the art. As an example, the material of the base film includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polyphenylene sulfide, polyimide, polystyrene, polytetrafluoroethylene, polymethyl methacrylate, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, cellulose, etc. The technicians in this field determine whether the ceramic layer and / or the rubber layer are provided on the base film according to the needs.

[0070] Preferably, the thickness of the ceramic layer is 0.3 μm-4 μm; it should be noted that the thickness of the ceramic layer refers to the thickness of the ceramic layer located on one side of the diaphragm. As an example, the thickness of the ceramic layer is 0.3 μm, 0.9 μm, 1.5 μm, 2.1 μm, 2.7 μm, 3.3 μm, 4.0 μm, or within the range of any two of the above values. It is understood that the ceramic layer can be a single layer or a multilayer structure.

[0071] Preferably, the peel strength between the ceramic layer and the base film is higher than 10 N / m; as an example, the peel strength between the ceramic layer and the base film is 11 N / m, 13 N / m, 15 N / m, 17 N / m, 19 N / m, 21 N / m, 23 N / m, 25 N / m or within the range of any two of the above values.

[0072] Preferably, the components of the ceramic layer include inorganic particles and a binder; the components of the ceramic layer include inorganic particles and a binder, and optionally, the mass ratio of the inorganic particles to the binder is (40-95):(5-60); the inorganic particles include at least one of boehmite, aluminum oxide, barium sulfate, magnesium oxide, magnesium hydroxide, silicon dioxide, tin oxide, titanium oxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, cerium dioxide, zirconium titanate, barium titanate and magnesium fluoride; the binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene and polyhexafluoropropylene.

[0073] Preferably, the glue coating layer is arranged on the surface of the ceramic layer.

[0074] Preferably, a ceramic layer and a rubber coating layer are sequentially arranged on the surface of the base film from the inside to the outside.

[0075] Preferably, the thickness of the adhesive layer is 0.3 μm-6 μm; as an example, the thickness of the adhesive layer is 0.3 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, or within a range formed by any two of the above values. It should be noted that the thickness of the adhesive layer refers to the thickness of the adhesive layer on the same side of the base film.

[0076] Preferably, the peel strength between the adhesive layer and the base film is higher than 10 N / m. As an example, the peel strength between the adhesive layer and the base film is 11 N / m, 13 N / m, 15 N / m, 17 N / m, 19 N / m, 21 N / m, 23 N / m, 25 N / m, or within a range formed by any two of the above values.

[0077] In an optional embodiment, the coating layer is a polymer coating, the polymer is granular or non-granular, and the particle size can be the same or different; the polymer is a common compound in the art; for example, the polymer includes a copolymer or homopolymer formed by at least one monomer of acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, butyl acrylate, ethylhexyl acrylate, styrene, α-methylstyrene, vinyltoluene, ethylene, vinyl acetate, acrylonitrile, vinylidene fluoride, hexafluoropropylene, and chlorophthalic anhydride; the polymer can also be at least one of polyetherimide, polyamideimide, polyimide, and a copolymer of vinylidene fluoride and hexafluoropropylene.

[0078] In an optional embodiment, the tensile strength of the diaphragm in the TD direction is 1200-7000 kgf / cm 2The tensile strength of the diaphragm in the MD direction is 1200-7000kgf / cm 2 and / or,

[0079] The elongation at break of the separator in the TD direction is greater than 30%, and the elongation at break of the separator in the MD direction is greater than 30%; and / or,

[0080] The puncture strength of the diaphragm is >120 gf.

[0081] It is understandable that the separator has better tensile strength and elongation at break, which can enable it to have better bonding with the negative electrode plate.

[0082] It should be noted that the tensile strength of the diaphragm is tested and obtained according to a method known in the art; for example, referring to the GB-228-87 test method, the test parameters are set as a gauge length of 50 mm and a tensile speed of 50 mm / min.

[0083] The puncture strength is obtained by testing according to methods known in the art. The results of different testing methods are basically consistent. Here is one testing method, for example: the length and width of the sample ≥ 80mm×80mm, the sample is installed in the testing machine, and the speed is adjusted to 100mm / min for testing.

[0084] As an example, the tensile strength of the separator in the TD direction is 1200 kgf / cm 2 、1500kgf / cm 2 、2000kgf / cm 2 、2500kgf / cm 2 、3000kgf / cm 2 、3500kgf / cm 2 、4000kgf / cm 2 、4500kgf / cm 2 、5000kgf / cm 2 、5500kgf / cm 2 、6000kgf / cm 2 、6500kgf / cm 2 、7000kgf / cm 2 Or within the range of any two of the above values. The tensile strength of the diaphragm in the MD direction is 1200kgf / cm 2 、1500kgf / cm 2 、2000kgf / cm 2 、2500kgf / cm 2 、3000kgf / cm 2 、3500kgf / cm 2 、4000kgf / cm 2、4500kgf / cm 2 、5000kgf / cm 2 、5500kgf / cm 2 、6000kgf / cm 2 、6500kgf / cm 2 、7000kgf / cm 2 Or within the range formed by any two of the above values. The elongation at break of the separator in the TD direction is 31%, 35%, 40%, 45%, 50%, or within the range formed by any two of the above values. The elongation at break of the separator in the MD direction is 31%, 35%, 40%, 45%, 50%, or within the range formed by any two of the above values. The puncture strength of the separator is 125gf, 130gf, 135gf, 140gf, 145gf, 150gf, or within the range formed by any two of the above values.

[0085] In an optional embodiment, the thermal shrinkage of the diaphragm in the TD direction (105°C 1h) is ≤10%, and the thermal shrinkage in the MD direction (105°C 1h) is ≤10%; the friction coefficient is 0.2-0.7; the membrane rupture temperature is >150°C; the closed cell temperature is ≤147°C; the porosity is 25%-50%; and the air permeability is 50-250s / 100cc, which affects the expansion and contraction during the charge and discharge process.

[0086] It should be noted that the thermal shrinkage is obtained by testing according to methods known in the art, and the results of different testing methods are basically the same. One testing method is listed, but not limited to the following method. First, the diaphragm sample to be cut is flatly clamped in A4 paper, placed in a punching mold and punched into a specification of 100×100mm; secondly, the clamp is covered on the diaphragm, a line is drawn in the empty space of the clamp, and the length of the line is measured using a 2.5D microscope, and the horizontal and vertical lengths are recorded; then the diaphragm sample clamped by A4 paper is placed in an oven and baked at 105°C for 1h. After cooling for 10min, the diaphragm is immediately measured with a microscope and the thermal shrinkage rate is calculated; the calculation formula for the diaphragm shrinkage rate is:

[0087] Transverse direction (TD) = (width before baking - width after baking) / width before baking × 100%

[0088] Machine direction (MD) = (length before baking - length after baking) / length before baking × 100%.

[0089] Friction coefficient: A dynamic friction coefficient tester is used, and the test method is as follows: cut a current collector with a length of 100 mm and a width of 80 mm, place it on a smooth plane, take a 75mm×75mm diaphragm, fix it on a 65mm×65mm slider, and move the slider forward at a constant speed of 100mm / min. The friction force is measured and then the dynamic friction coefficient is obtained.

[0090] Air permeability: Use a membrane air permeability tester to test the membrane air permeability.

[0091] Membrane rupture temperature and closed-cell temperature: First, you need to build a battery for testing, which will be used for subsequent heating and resistance measurement; secondly, place the test battery in a temperature-controlled environment, gradually heating it from 30°C to 200°C. During the heating process, you need to record the temperature of the test battery and its corresponding resistance value every 5 seconds. Finally, based on the recorded data, draw the temperature-resistance curve of the test battery. By calculating the resistance change at intervals of 5 seconds, when the resistance value increases by more than 50Ω for the first time or the resistance value decreases by more than 50Ω for the first time, determine the closed-cell temperature and membrane rupture temperature, respectively.

[0092] In an optional embodiment, the battery further comprises an electrolyte; the electrolyte comprises an electrolyte salt and a solvent; the electrolyte further comprises an additive. It is understandable that the electrolyte is a common raw material for preparing batteries in the art.

[0093] In an alternative embodiment, the electrolyte salt comprises lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4 ), lithium perchlorate (LiClO 4 ) lithium hexafluoroarsenate (LiAsF 6 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO 2 F 2 ), at least one of lithium difluorobis(oxalate) phosphate (LiDFOP) and lithium tetrafluorooxalate phosphate (LiTFOP).

[0094] In an optional embodiment, the solvent includes at least one of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).

[0095] In an optional embodiment, the additive includes a film-forming additive on the surface of the negative electrode, a film-forming additive on the surface of the positive electrode, and a film-forming additive on the surface of the positive and negative electrode current collectors; and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc. The additive may be a nitrile compound such as a dinitrile compound, a trinitrile compound, a cyclic carbonate having a carbon-carbon double bond, a fluorinated chain carbonate, a fluorinated cyclic carbonate, or a sulfur-oxygen double bond compound, and the following compounds are listed here:

[0096] The dinitrile compounds include, but are not limited to, succinonitrile, glutaronitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 1,8-dicyanooctane, 1,9-dicyanononane, 1,10-dicyanodecane, 1,12-dicyanododecane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylvaleronitrile, 2,2,4,4-tetramethyl Glutaronitrile, 1,5-dicyanopentane, 2,6-dicyanoheptane, 2,7-dicyanooctane, 2,8-dicyanononane, 1,6-dicyanodecane, 1,2-dicyanobenzene, 1,3-dicyanobenzene, 1,4-dicyanobenzene, 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, ethylene glycol di(2-cyanoethyl) ether, diethylene glycol di(2-cyanoethyl) ether ) ether, triethylene glycol di(2-cyanoethyl) ether, tetraethylene glycol di(2-cyanoethyl) ether, 3,6,9,12,15,18-hexaoxaicosanoic acid dinitrile, 1,3-bis(2-cyanoethoxy)propane, 1,4-bis(2-cyanoethoxy)butane, 1,5-bis(2-cyanoethoxy)pentane, ethylene glycol di(4-cyanobutyl) ether, 1,4-dicyano-2-butane 1,4-dicyano-2-methyl-2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3-dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6-dicyano-3-hexene, 1,6-dicyano-2-methyl-3-hexene or 1,6-dicyano-2-methyl-5-methyl-3-hexene.

[0097] The trinitrile compounds include, but are not limited to, 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane, or 1,2,5-tris(cyanoethoxy)pentane.

[0098] Cyclic carbonates having a carbon-carbon double bond include, but are not limited to, vinylene carbonate, methyl vinylene carbonate, ethyl vinylene carbonate, 1,2-dimethyl vinylene carbonate, 1,2-diethyl vinylene carbonate, fluorovinylene carbonate, trifluoromethyl vinylene carbonate; vinyl ethylene carbonate, 1-methyl-2-vinylethylene carbonate, 1-ethyl-2-vinylethylene carbonate, 1-n-propyl-2-vinylethylene carbonate, 1-methyl-2-vinylethylene carbonate, 1,1-divinylethylene carbonate, 1,2-divinylethylene carbonate; 1,1-dimethyl-2-methyleneethylene carbonate, 1,1-diethyl-2-methyleneethylene carbonate.

[0099] The fluorinated chain carbonates include, but are not limited to, fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate or bis(trifluoroethyl) carbonate.

[0100] Fluorinated cyclic carbonates include, but are not limited to, fluoroethylene carbonate, 4,4-difluoroethylene carbonate, 4,5-difluoroethylene carbonate, 4-fluoro-4-methylethylene carbonate, 4,5-difluoro-4-methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, 4,4-difluoro-5-methylethylene carbonate, 4-(fluoromethyl)-ethylene carbonate, 4-(difluoromethyl)-ethylene carbonate, 4-(trifluoromethyl)-ethylene carbonate, 4-(fluoromethyl)-4-fluoroethylene carbonate, 4-(fluoromethyl)-5-fluoroethylene carbonate, 4-fluoro-4,5-dimethylethylene carbonate, 4,5-difluoro-4,5-dimethylethylene carbonate, 4,4-difluoro-5,5-dimethylethylene carbonate.

[0101] The compounds containing sulfur-oxygen double bonds include, but are not limited to, cyclic sulfates, chain sulfates, chain sulfonates, cyclic sulfonates, chain sulfites, cyclic sulfites, chain sulfites, chain sulfones, cyclic sulfones, and the like.

[0102] It should be noted that one or more auxiliary agents can be selected during use, depending on the usage requirements.

[0103] Example 1

[0104] This embodiment provides a battery, including:

[0105] (1) Positive electrode

[0106] like Figure 1 As shown, the positive electrode sheet includes a positive electrode current collector aluminum foil 11 and a positive electrode active material layer 12 arranged on both sides of the positive electrode current collector; the positive electrode active material LiCoO 2, conductive agent SP and binder PVDF are mixed, NMP solvent is added, and the mixture is stirred thoroughly to form a uniform slurry, which is then coated on both sides of the positive electrode current collector, dried to remove the solvent, and the positive electrode sheet is obtained through rolling, slitting and sheeting. The tensile strength and elongation of the positive electrode current collector are shown in Table 1.

[0107] (2) Negative electrode

[0108] like Figure 2 As shown, the negative electrode sheet includes a negative electrode current collector 21 and a negative electrode active material layer 22 arranged on both sides of the negative electrode current collector; the negative electrode active material graphite, the conductive agent SP and the binder SBR are mixed according to a mass ratio of 97.2:2.3:0.05, and deionized water solvent is added, and the slurry is fully stirred to form a uniform slurry, which is coated on both sides of the negative electrode current collector, and the solvent is removed by drying, and the negative electrode sheet is obtained through rolling, slitting and sheeting processes. The tensile strength and elongation of the negative electrode current collector are shown in Table 1, and the intensity of the X-ray diffraction peak of the (111) crystal plane of the negative electrode current collector is shown in Table 1.

[0109] (3) Electrolyte

[0110] Ethylene carbonate (EC), propylene carbonate (PC), ethyl propionate (EP), and propyl propionate (PP) solvents were mixed evenly at a mass ratio of 15:10:30:35, and LiPF was slowly added to the mixed solution. 6 , fluoroethylene carbonate, 1,3-propane sultone and lithium difluorooxalatoborate, stirred evenly to obtain an electrolyte. 6 The content of is 15wt%, the content of fluoroethylene carbonate is 10wt%, the content of 1,3-propane sultone is 5wt%, and the content of lithium difluorooxalatoborate is 1wt%.

[0111] (4) Diaphragm

[0112] 80 parts by mass of boehmite (particle size DV90 = 0.2 μm, DV10 = 0.1 μm) and 20 parts by mass of poly(methyl)acrylate were added to 900 parts by mass of deionized water, and mixed evenly to obtain a mixed slurry 1, which was coated on the first surface of the base film 31 by micro-gravure printing, and dried to obtain a diaphragm having a ceramic layer 32. 100 parts by mass of polyvinylidene fluoride were added to 900 parts by mass of NMP, and mixed evenly to obtain a slurry 2, which was coated on the surface of the ceramic layer and the second surface of the base film by micro-gravure printing to form a coating layer 33, the structure of which is as follows: Figure 3 As shown. In the separator, the base film is a wet-process PE substrate with a thickness of 5 μm. The porosity D, air permeability E, pore size distribution F, and thickness H of the separator are shown in Table 1.

[0113] (5) Lithium-ion battery

[0114] like Figure 4 As shown, the positive electrode sheet, the separator and the negative electrode sheet are wound into a bare core in sequence, the bare core is placed in an outer packaging foil, top-sealed and side-sealed, baked to remove moisture, and then injected with electrolyte, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained. Among them, the formation process: 0.1C constant current charging to 4% SOC, and then 0.2C constant current charging to 10% SOC.

[0115] Example 2-19

[0116] Examples 2-19 provide a battery, which is prepared according to Example 1. The main difference from Example 1 is that the tensile strength A of the negative electrode current collector is 1 , elongation of negative electrode current collector B 1 , tensile strength of positive electrode current collector A 2 , elongation of positive electrode current collector B 2 , the bonding strength C between the separator and the negative electrode sheet 1 , the intensity of the X-ray diffraction peak of the negative electrode current collector crystal surface I, the pore size distribution F of the separator, the air permeability value E of the separator, the porosity D of the separator, and the bonding strength C between the separator and the negative electrode plate 1 , the thickness H of the diaphragm is different, and the above parameters of each embodiment are shown in Table 1.

[0117] Comparative Examples 1-4

[0118] Comparative Examples 1-4 provide a battery, which is prepared with reference to Example 1, and the main difference from Example 1 is that the tensile strength A of the negative electrode current collector is 1 , elongation of negative electrode current collector B 1 , tensile strength of positive electrode current collector A 2 , elongation of positive electrode current collector B 2 , the bonding strength C between the separator and the negative electrode sheet 1 , the intensity of the X-ray diffraction peak of the negative electrode current collector crystal surface I, the pore size distribution F of the separator, the air permeability value E of the separator, the porosity D of the separator, and the bonding strength C between the separator and the negative electrode plate 1 , the thickness H of the diaphragm is different, and the above parameters of each embodiment are shown in Table 1.

[0119] Test Case

[0120] This test example provides the performance of the batteries of each embodiment and comparative example, as follows:

[0121] (1) Test method for membrane porosity: Stack the membrane into 6 layers, flatten them, press them tightly, and remove the air in the membrane. Cut the membrane sample and obtain the area S of the membrane sample after measurement. Measure the thickness of the membrane sample 10 times and calculate the average value B. Use an electronic balance to measure the weight of the membrane sample 3 times and obtain the average value M. Calculate the membrane porosity according to the following formula:

[0122]

[0123] (2) Test method for tensile strength and elongation of positive electrode current collector: GB-228-87 test method was used for testing, and the test parameters were set as a gauge length of 50 mm and a tensile speed of 10 mm / min.

[0124] (3) Test method for tensile strength and elongation of negative electrode current collector: GB-228-87 test method was used for testing, with test parameters of gauge length 50 mm and tensile speed 50 mm / min.

[0125] (4) Negative current collector XRD test method: A Rigaku type X-ray diffractometer was used to characterize the physical phase and analyze the crystal surface of the negative current collector sample. The surface of the negative current collector to be tested was cleaned with 10 vol.% dilute sulfuric acid and anhydrous ethanol solution in turn, and the test was performed after being blown dry with cold air. The test conditions were: using a copper Kα target (λ = 0.15406nm), an operating voltage of 40kV, a scanning angle range of 20-100°, and a scanning rate of 0.02° / s.

[0126] (5) Cycle performance test method: The battery is left at rest for 10 minutes at 25℃±3℃, then discharged at a rate of 0.2C to 3.0V, and left at rest for 10 minutes after reaching the target voltage value; then charged at a constant current of 0.8C, and left at rest for 10 minutes after cutting off 0.05C; then discharged at a constant current of 0.5C to 3.0V, and left at rest for 10 minutes; then fully charged according to the specification standard, cut off 0.05C, and left at rest for 10 minutes. The charging and discharging steps at 25℃ are cycled 20 times, and the battery is charged at a constant current of 0.8C, and removed from the stage after cutting off 0.05C. The battery is disassembled in an environment with a dew point of -35℃ to observe whether the diaphragm is separated from the negative electrode plate and whether the negative electrode plate is deformed. Among them, as long as the diaphragm is separated from the negative electrode plate, it is considered to be separated; the standard for the deformation of the negative electrode plate: the surface area of ​​the plate after charging changes compared with the initial state before charging, which is considered to be deformed.

[0127] (6) Cycle expansion rate test method: After the lithium-ion battery is fully discharged, it is charged to a full charge state at a constant current and then disassembled to measure the surface area of ​​the electrode parallel to the width of the battery cell. When the 300th cycle is measured, the surface area of ​​the electrode parallel to the width of the battery cell is measured, and the expansion rate is calculated by the following formula:

[0128]

[0129] Table 1 Parameters of each embodiment

[0130]

[0131]

[0132] Table 2 Test results of various embodiments

[0133]

[0134] According to the above results, it can be seen that A 1 ≥300MPa; B 1 Satisfaction: 2% ≤ B 1 %≤10%; A 2 Satisfaction: A 2 ≥180MPa; B 2 Satisfaction: 1% ≤ B 2 %≤10%; C 1 Satisfy: 1N / m≤C 1 ≤80N / m, and make it satisfy the relationship 1, which can make the negative electrode plate resist the deformation caused by lithium removal and lithium insertion, reduce the deformation of the negative electrode plate, prevent the plate from large irreversible expansion, reduce the separation of the negative electrode plate and the diaphragm, prevent the battery from short circuit, and improve the safety performance of the battery. In combination with Examples 17 and 19, the factors such as the crystal surface strength of the negative electrode collector, the pore size distribution of the diaphragm, the porosity of the diaphragm, the air permeability of the diaphragm, the bonding strength between the diaphragm and the negative electrode plate of the present invention are satisfied with the relationship 2, which can improve the bonding between the diaphragm and the negative electrode plate, reduce expansion and contraction, and thus avoid the problem of the negative electrode plate falling off. In combination with Example 18, the present invention makes I>10000counts, 20nm≤F≤90nm, 50s / 100cc≤E≤250s / 100cc, 25%≤D%≤50%, 1N / m≤C 1 ≤80N / m, which helps to further reduce expansion and contraction and prevent problems such as the negative electrode sheet falling off.

[0135] Combined with Comparative Examples 1-4, the present invention A 1 ≥300MPa, 2%≤B 1 %≤10%,A 2 ≥180MPa, 1%≤B 2 %≤10%,1N / m≤C 1 ≤80N / m, and satisfying the relation 1, the negative electrode plate can resist the deformation caused by lithium removal and lithium insertion, reduce the deformation of the negative electrode plate, prevent the plate from large irreversible expansion, reduce the separation of the negative electrode plate and the diaphragm, prevent the battery from short circuit, and improve the safety performance of the battery.

[0136] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet and a separator arranged between the positive electrode sheet and the negative electrode sheet; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active layer located on at least one side of the positive electrode current collector; the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer located on at least one side of the negative electrode current collector; the tensile strength A1 of the negative electrode current collector, the elongation B1% of the negative electrode current collector, the tensile strength A2 of the positive electrode current collector, the elongation B2% of the positive electrode current collector, and the bonding strength C1 of the separator and the negative electrode sheet satisfy the relationship 1: The A1 satisfies: A1≥300MPa; the B1 satisfies: 2%≤B1%≤10%; the A2 satisfies: A2≥180MPa; the B2 satisfies: 1%≤B2%≤10%; the C1 satisfies: 1N / m≤C1≤80N / m.

2. The lithium-ion battery according to claim 1, characterized in that The A1 satisfies: 300MPa≤A1≤1000MPa; the A2 satisfies: 180MPa≤A2≤350MPa.

3. The lithium ion battery according to claim 1 or 2, characterized in that: The surface density of the negative electrode current collector is not less than 26 mg / m 2 and / or, The thickness of the negative electrode current collector is not less than 3 μm.

4. The lithium ion battery according to claim 1 or 2, characterized in that: The surface density of the positive electrode current collector is not less than 16 mg / m 2 and / or, The thickness of the positive electrode current collector is not less than 6 μm.

5. The lithium ion battery according to claim 1 or 2, characterized in that: The negative electrode current collector contains a doping element; the doping element includes at least one of Cr, Fe, Mg, Mn, Sb, Si, Sn, Ti and Zn; and / or, The content of doping elements in the negative electrode current collector is not higher than 1000 ppm; and / or, The positive electrode current collector contains a doping element; the doping element includes at least one of Cr, Fe, Mg, Mn, Sb, Si, Sn, Ti and Zn; and / or, The content of the doping element in the positive electrode current collector is not higher than 10000 ppm.

6. The lithium-ion battery according to claim 1, characterized in that The negative electrode current collector and the separator satisfy the relationship 2: Wherein, I is the intensity of the X-ray diffraction peak of the negative electrode current collector (111) crystal plane, and I>10000 counts; F is the pore size distribution of the diaphragm, and F satisfies: 20nm≤F≤90nm; E is the air permeability value of the diaphragm, and E satisfies: 50s / 100cc≤E≤250s / 100cc; D is the porosity of the diaphragm, and D satisfies: 25%≤D%≤50%; C1 is the bonding strength between the diaphragm and the negative electrode plate, and C1 satisfies: 1N / m≤C1≤80N / m, and the thickness H of the diaphragm satisfies: 5μm≤H≤15μm.

7. The lithium-ion battery according to claim 6, characterized in that: The EF satisfies: EF>1200.

8. The lithium ion battery according to claim 1 or 6, characterized in that: The diaphragm includes a base membrane; Preferably, the base film has a thickness of 3 μm-16 μm, a porosity of 25%-50%, an air permeability of 50s / 100cc-250s / 100cc, and a pore size distribution of 20nm-90nm.

9. The lithium-ion battery according to claim 8, characterized in that: The diaphragm further comprises a coating, the coating is located on at least one surface of the base film, and the coating comprises at least one of a ceramic layer and a rubber coating layer; Preferably, the peel strength between the ceramic layer and the base film is higher than 10N / m; Preferably, the glue coating layer is arranged on the surface of the ceramic layer; Preferably, the peel strength between the adhesive layer and the base film is higher than 10 N / m.

10. The lithium ion battery according to claim 1 or 6, characterized in that: The elongation at break of the separator in the TD direction is greater than 30%, and the elongation at break of the separator in the MD direction is greater than 30%; and / or, The tensile strength of the diaphragm in the TD direction is 1200-7000kgf / cm 2 The tensile strength of the diaphragm in the MD direction is 1200-7000kgf / cm 2 and / or, The puncture strength of the diaphragm is >120 gf.

Citation Information

Patent Citations

  • Electrolytic copper foil, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    CN104583461A

  • Negative pole piece and lithium metal battery

    CN112563461A

  • Secondary battery and electronic device

    CN116830347A

  • Secondary battery and electric device

    CN116979221A

  • Novel positive electrode composite current collector, preparation method and application thereof

    CN117293324A

Cited By

  • Lithium ion battery, battery assembly and electric device

    CN121215846A

  • Current collector, preparation method therefor, battery cell, secondary battery and electrical apparatus

    WO2026171228A1